Examining job satisfaction factors toward retaining Malaysian TVET instructors in the teaching profession - Omar, Muhd Khaizer; Mat Rashid, Abdullah; Mohd Puad, Mohd Hazwan (Science Publishing Corporation, 2018)
The teaching profession in Malaysia has continued to be valued due to the continuous effort and commitment by teachers within the education profession and their desire to benefit better education for future generations. Indeed, the teaching profession has evolved to become a recognised benchmark towards the nation’s vision to develop human resource capital. However, despite the recognition, teachers are noticeably struggling in their attempt to provide high-quality teaching services. Many studies have reported many of the issues within the teaching profession and environment that exists. Many of the issues include severe depression, anxiety, demotivation, and behavioural issues. Consequently, many of these issues also become the reasons why teachers inevitably leave their chosen profession, either voluntarily or pressured by the educational environment and system. As a result, a study to understand the issues for their departure, and more importantly the factors contributing to job satisfaction and retention have investigated in this study. A target population targeting Malaysian training instructors at the Technical and Vocational Education and Training (TVET) educational institutions were selected to participate in a survey. Descriptive and correlational studies were employed to determine job satisfaction the factors among TVET instructors and to identify the factors contributing towards job satisfaction and retention. The findings indicate that most instructors are satisfied with their teaching job. However, many are struggling and not coping with voracious issues brought about through present workloads, student disciplinary problems, and vague expectations from key stakeholders in the TVET system. The findings from this study will further help in determining the perspectives of the instructors and the factors that have attracted them to remain in their chosen profession and to enable them to enjoy their teaching profession and career.